2016
DOI: 10.1111/tger.12010
|View full text |Cite
|
Sign up to set email alerts
|

… but you are not German.” – Afro‐German culture and literature in the German language classroom

Abstract: Units and classes dedicated to multiculturalism in Germany have predominantly focused on Turkish‐German literature and culture. Afro‐Germans have been a minority whose culture and literature have only marginally been included in German classes, even though Afro‐Germans have been a part of Germany for centuries and have undergone efforts at establishing themselves as an organized cultural group. This article argues for a stronger focus on Afro‐German culture in German classes by providing a brief overview of Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Cobb traced the impact of different “Afro” connections to the Spanish‐speaking world. Similar efforts followed for multiple languages: French (e.g., Gross, 2007; Murphy, 2015); German (e.g., Chen, 2022; Divers, 1995; Nenno, 2019; Putnam, 2008; Schenker & Munro, 2016; Uca et al, 2022; Willeke, 2001); Latin (e.g., Kennedy, 2022; Masciantonio, 1977); and Spanish (e.g., Granda, 2021; Rogers, 2006; Watson, 2013). These articles presented lessons that engaged students with race as a theme in authentic texts such as film (e.g., Libbon, 2008; Ruggiero, 2015), classical and contemporary music (e.g., Howards, 2014; Sosulski, 2013), and canonical literature (e.g., Frackman, 2011; Hopkins, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Cobb traced the impact of different “Afro” connections to the Spanish‐speaking world. Similar efforts followed for multiple languages: French (e.g., Gross, 2007; Murphy, 2015); German (e.g., Chen, 2022; Divers, 1995; Nenno, 2019; Putnam, 2008; Schenker & Munro, 2016; Uca et al, 2022; Willeke, 2001); Latin (e.g., Kennedy, 2022; Masciantonio, 1977); and Spanish (e.g., Granda, 2021; Rogers, 2006; Watson, 2013). These articles presented lessons that engaged students with race as a theme in authentic texts such as film (e.g., Libbon, 2008; Ruggiero, 2015), classical and contemporary music (e.g., Howards, 2014; Sosulski, 2013), and canonical literature (e.g., Frackman, 2011; Hopkins, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the incorporation of Afro-German literature into German Studies curricula has been identified as slow and insufficient (Johnson, 2001). Calls to include works by Afro-German authors are largely ignored and most HEI curricula lack a systematic incorporation of texts by Afro-Germans (Schenker & Munro, 2013). In addition, a search for "mobilität" (mobility) resulted in 143 program matches, though the vast majority were engineering and technology-related.…”
Section: University Curricula: Ethnic and Identity Studies Departmentsmentioning
confidence: 99%